2018
DOI: 10.1136/bmjopen-2018-022087
|View full text |Cite
|
Sign up to set email alerts
|

Models of suicide in elderly: a protocol for a systematic review

Abstract: IntroductionThe rates of suicide in the elderly population are generally higher than other age groups. Models of suicide that explain the phenomenon of suicide in later life may have research, clinical and educational implications for the field of ageing. The primary purpose of this systematic review is to identify and review existing models of suicide that have a particular focus on the elderly.Methods and analysisThe authors intend reviewing the findings of observational studies including cohort studies, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In previous studies [ 8 , 9 ], suicide prevention interventions in the elderly population were found to reduce suicidal thoughts and suicide rates. For this reason, interest in the elderly suicide model has increased, including the development of protocols for models that describe and predict suicide in the elderly [ 10 ]. Thus, one of the common methods is to use a measurement tool.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [ 8 , 9 ], suicide prevention interventions in the elderly population were found to reduce suicidal thoughts and suicide rates. For this reason, interest in the elderly suicide model has increased, including the development of protocols for models that describe and predict suicide in the elderly [ 10 ]. Thus, one of the common methods is to use a measurement tool.…”
Section: Introductionmentioning
confidence: 99%
“…[2]. Suicides among the elderly may be more frequent than in other age groups, and for example in Korea these rates are up to three times higher [3,4]. The reasons that lead the elderly to attempt suicide may be related to aging stressors, such as deteriorating health or problems with adapting to the aging process [5].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons that lead the elderly to attempt suicide may be related to aging stressors, such as deteriorating health or problems with adapting to the aging process [5]. One of the most important risk factors for suicide are mental diseases, especially depression, anxiety and bipolar disorder [4,6]. Multi-disease patients are particularly prone to depression due to a reduced standard of living and the use of drugs that can cause depression symptoms such as B-blockers, digitalis glycosides, NSAIDs, opioids, ACEI, Calcium Channel Blockers, Corticosteroids, diuretics, Levodopa, benzodiazepines and others [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors are a family history of suicide, previous suicide attempts, isolation, loss, physical illnesses, and easy access to lethal methods. The risk of suicide increases with age in almost all countries, and suicide rates reach 48.7/ 100 000 for older Caucasian men in the United States and 140/100 000 for older men in rural China (6)(7)(8)(9)(10). Older adults may be more prone to self-harming behavior because of the higher prevalence and coexistence of many social and clinical factors: financial issues, social isolation, bereavement, dependence, physical and mental illnesses, and so on (11).…”
Section: Introductionmentioning
confidence: 99%